Lysicamine Reduces Protein Kinase B (AKT) Activation and Promotes Necrosis in Anaplastic Thyroid Cancer - Mariana Teixeira Rodrigues; Ana Paula Picaro Michelli; Gustavo Felisola Caso; Paloma Ramos de Oliveira; Dorival Mendes Rodrigues-Junior; Mirian Galliote Morale; Joel Machado Júnior; Karina Ramalho Bortoluci; Rodrigo Esaki Tamura; Tamiris Reissa Cipriano da Silva; Cristiano Raminelli; Eric Chau; et al. (MDPI AG, 2023)
Anaplastic thyroid cancer (ATC) is an aggressive form of thyroid cancer (TC), accounting for 50% of total TC-related deaths. Although therapeutic approaches against TC have improved in recent years, the survival rate remains low, and severe adverse effects are commonly reported. However, unexplored alternatives based on natural compounds, such as lysicamine, an alkaloid found in plants with established cytotoxicity against breast and liver cancers, offer promise. Therefore, this study aimed to explore the antineoplastic effects of lysicamine in papillary TC (BCPAP) and ATC (HTH83 and KTC-2) cells. Lysicamine treatment reduced cell viability, motility, colony formation, and AKT activation while increasing the percentage of necrotic cells. The absence of caspase activity confirmed apoptosis-independent cell death. Necrostatin-1 (NEC-1)-mediated necrosome inhibition reduced lysicamine-induced necrosis in KTC-2, suggesting necroptosis induction via a reactive oxygen species (ROS)-independent mechanism. Additionally, in silico analysis predicted lysicamine target proteins, particularly those related to MAPK and TGF-β signaling. Our study demonstrated lysicamine's potential as an antineoplastic compound in ATC cells with a proposed mechanism related to inhibiting AKT activation and inducing cell death.